DEVELOPMENT AND VALIDATION OF UV-SPECTROPHOTOMETRIC METHODS FOR SIMULTANEOUS ESTIMATION OF CETIRIZINE HYDROCHLORIDE AND PHENYLEPHRINE HYDROCHLORIDE IN TABLETS (International Journal of Pharmaceutical Sciences and Drug Research, 2012)
Without resolving mixtures of Cetirizine hydrochloride and Phenylephrine hydrochloride, simultaneous estimation has been successfully achieved by spectrophotometry. First method, simultaneous equation method employs formation and solving of mathematical simultaneous equation using 237.5 nm and 232.0 nm as the λmax of Phenylephrine hydrochloride and Cetirizine hydrochloride respectively in distilled water. Second method is first order derivative spectroscopy, wavelengths selected for quantitation were 232.0 nm for Phenylephrine hydrochloride (zero cross for Cetirizine hydrochloride) and 242.5 nm for Cetirizine hydrochloride (zero cross for Phenylephrine hydrochloride). These methods were validated as per ICH norms. Calibration curves were linear over the concentration ranges of 12-60 μg/ml for both drugs and for both methods. The validation study is statistically significant as all the statistical parameters are within the acceptance range (% RSD < 2.0 and S.D. < 2.0) for both accuracy and precision. The methods are successfully applied to pharmaceutical formulation, with no interference from excipients as indicated by the recovery study. The proposed methods are simple, rapid, economic and accurate for routine simultaneous estimation of Phenylephrine hydrochloride and Cetirizine hydrochloride. Simultaneous equation method was successfully applied to carry out dissolution study of commercial tablet formulation by using USP II dissolution test apparatus.